Questioning Ecological Justice in Indonesian Forestry Regulations - Sholahuddin Al-Fatih; Clarizze Yvoine Mirielle; Enas Qutieshat; Uzoho Kelechi; Narzullaev Olim Kholmamatovich (Contrarius, 2026)
This study examines forestry regulation from the perspective of ecological justice by analysing the relationship between state control, environmental protection, and the rights of indigenous peoples. The research employs a normative legal research method based on secondary data comprising primary and secondary legal materials. The approaches adopted include statutory, conceptual, and comparative approaches to assess forestry governance in Indonesia and to compare it with Canada. The findings indicate that, at the normative level, forestry regulations have accommodated the principles of sustainability and social justice; however, their implementation continues to face challenges, including centralised authority, tenure conflicts, and environmental degradation. The comparative analysis demonstrates the importance of integrating ecosystem protection, recognising the rights of indigenous peoples, and ensuring public participation. Accordingly, the reconstruction of forestry regulation is required to strengthen participation, to reaffirm the meaning of state control as a public mandate, and to enhance enforcement mechanisms grounded in environmental restoration for the benefit of intergenerational sustainability.